2018
DOI: 10.1016/j.braindev.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Fosphenytoin vs. continuous midazolam for pediatric febrile status epilepticus

Abstract: Our results suggest that 1) the efficacy of fPHT and cMDL is similar, although cMDL may prevent the need for BCT compared with fPHT, and 2) fPHT is relatively safe as a second-line treatment for pediatric SE in patients who do not require BCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The efficacy of second-line drugs such as fPHT, valproate, and levetiracetam has been reported to be similar in patients with benzodiazepine resistant SE [ 17 ]. Moreover, we have previously reported that there is no difference in the efficacy of fPHT and MDL ci in pediatric patients with benzodiazepine resistant SE [ 18 ]. Previous studies showed that the efficacy of several second-line agents was similar in patients with benzodiazepine resistant SE, including febrile SE.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of second-line drugs such as fPHT, valproate, and levetiracetam has been reported to be similar in patients with benzodiazepine resistant SE [ 17 ]. Moreover, we have previously reported that there is no difference in the efficacy of fPHT and MDL ci in pediatric patients with benzodiazepine resistant SE [ 18 ]. Previous studies showed that the efficacy of several second-line agents was similar in patients with benzodiazepine resistant SE, including febrile SE.…”
Section: Discussionmentioning
confidence: 99%
“…However, seizure control, seizure recurrence, seizure-free duration and intensive care unit and hospital stay were similar in both the groups [8]. In a pediatric study [9] comparing intravenous fPHT with midazolam infusion as a second line agent in febrile status, efficacy of both was found to be similar and the latter was found to be relatively safe. The proportion of patients requiring barbiturate coma, mechanical ventilation and inotropic support and having incomplete recovery from consciousness was also not significantly different between the groups [9].…”
mentioning
confidence: 99%